1975
DOI: 10.1542/peds.55.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous and Exogenous Insulin Responses in Patients With Cystic Fibrosis

Abstract: Eight male patients with cystic fibrosis, normal nutrition, normal physical activity, relatively mild pulmonary disease, no evidence of liver disease and no family history of diabetes mellitus underwent a series of carbohydrate tolerance tests in comparison with a group of 18 normal male subjects matched for age and body weight. Compared with the normal group, the patients with cystic fibrosis had significantly impaired glucose tolerance and significantly lower serum immunoreactive insulin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Th e production of insulin by non be ta cells ma y be sufficient to limit the progression from glucos e intolera nce to frank DM a nd pot entiall y for the a bse nce of ketoacidosis in CF/DM . Addition all y, we ha ve suggested that the peripher al tissue in C F ma y show increased insulin se ns itivity (100). Thi s ha s been extended by the ob ser vati on that monoc yte s from CF pati ents ha ve increased insulin binding because of an increased number of ce llular insulin receptor s (104,105).…”
Section: Discussionmentioning
confidence: 81%
“…Th e production of insulin by non be ta cells ma y be sufficient to limit the progression from glucos e intolera nce to frank DM a nd pot entiall y for the a bse nce of ketoacidosis in CF/DM . Addition all y, we ha ve suggested that the peripher al tissue in C F ma y show increased insulin se ns itivity (100). Thi s ha s been extended by the ob ser vati on that monoc yte s from CF pati ents ha ve increased insulin binding because of an increased number of ce llular insulin receptor s (104,105).…”
Section: Discussionmentioning
confidence: 81%